Anaesthesia management on pregnancy with co-morbid asthma undergoing non-obstetric surgery - Aryasa, Tjahja; Senapathi, Tjokorda GA; Ryalino, Christopher; Pranoto, Theodorus Pascalis Yullie (Bali Journal of Anesthesiology, 2019)
In the pregnancy process, there is a significant physiological change in the mother. Physiological changes, pre-pregnancy conditions, or those that arise during the pregnancy process will affect the delivery outcome. Also, it turns out that the presence of this preexisting condition will affect the outcome process, especially the anaesthetic technique used, the chosen anaesthetic technique is determined based on the age of the pregnancy, surgical procedures to be performed, surgery site, and overall patient condition. Whatever technique is selected, it must use the right method based on clinical decisions and accordingly to the existing guidelines. This condition is a challenge for an anesthesiologist.